“Conocimiento sobre contaminación microbiológica mediante aerosoles durante la COVID-19 en alumnos de Estomatología, Trujillo-2021” - Briones Socorro, María Jackeline Brizeth (2022)
The purpose of this observational, descriptive and cross-sectional study was to determine the level of knowledge about microbiological contamination by aerosols during COVID-19 of Stomatology students from Trujillo-2021 The sample consisted of a total of 141 students, 94 female (66,7%) and 47 male (33,3%); of which 70 (49,7%) correspond to the penultimate year and 71 (50,3%) correspond to the last year of study, to whom a virtual questionnaire of 15 questions was applied. It was found that the level of knowledge about microbiological contamination through aerosols during COVID-19 of Stomatology students from Trujillo-2021 was 43,3% with the "good" level, 48,2% with the "regular" level and 8,5% with the "bad" It is concluded that the level of knowledge about microbiological contamination by aerosols during COVID-19 of Stomatology students from Trujillo-2021 was mostly "regular".